GIS Applied to the Mapping of Land Use, Land Cover and Vulnerability in the Outcrop Zone of the Guarani Aquifer System - Santos, Rafael Goncalves [UNESP]; Sturaro, Jose Ricardo [UNESP]; Marques, Mara Lucia [UNESP]; Faria, Tiago Tadeu de [UNESP]; Drusa, M.; Marschalko, M.; Yilmaz, I; Segallini, A.; Ferrero, A. M.; Bednarik, M. (Elsevier B.V., 2015)
This study presents the vulnerability mapping of Guarani Aquifer System (GAS) in the municipality of Ribeirao Bonito, the central region of the state of Sao Paulo, through the application of Pesticide DRASTIC index assigned to the land use and land cover (LULC). The principal mapped activities confirm the agricultural potential in the municipality, justifying the implementation of Pesticide DRASTIC index. Based in the use of GIS, the seven spatial parameters were considered in the vulnerability mapping (Depth to water table, net Recharge, Aquifer media, Soil media, Topography, Impact of vadose zone, and hydraulic Conductivity). The results indicate a large presence of areas with high vulnerability, corresponding to 60.3% of the city. All potentially polluted lands showed more than half of their areas in high or moderate vulnerability region. This paper is an important tool of land use/land cover mapping in GAS recharge areas, highlighting the need of studies that consider the processes occurring in the surface and underground for the analysis of aquifers vulnerability. (C) 2015 Published by Elsevier B.V.
Keywords: Guarani aquifer system (GAS); aquifers vulnerability; land use and land cover; Ribeirao Bonito